Properties of a Saccharomyces cerevisiae mtDNA segment conferring high-frequency yeast transformation. - Hyman, B C (1982)
The bakers' yeast Saccharomyces cerevisiae is a facultative anaerobe, tolerant to mutations in its mitochondrial genome. Individual cytoplasmic petite mutants retain genetic information derived from any portion of the parenteral mtDNA, prompting questions concerning distribution of the DNA replication origin(s) on the yeast mitochondrial genome. The experiments described in this paper were designated to test the possibility of using high-frequency yeast transformation as a selection for yeast mtDNA sequences conferring autonomously replicating function. A complete petite mitochondrial genome was inserted into the yeast vector YIp5, and the hybrid plasmid (YRMp1) was used to transform yeast. YRMp1 promoted high-frequency transformation of both wild-type yeast cells and petite mutant hosts lacking mtDNA and was maintained in each of these strains as a high-copy-number extrachromosomal element. The stability and copy-number properties of YRMp1 are similar to those of YRp12, a recombinant plasmid containing a yeast chromosomal autonomously replicating sequence.